We could be so good : a novel - Sebastian, Cat (Avon, an imprint of HarperCollinsPublishers, 2023)
Nick Russo has worked his way from a rough Brooklyn neighborhood to a reporting job at one of the city's biggest newspapers. But the late 1950s are a hostile time for gay men, and Nick knows that he can't let anyone into his life. He just never counted on meeting someone as impossible to say no to as Andy. Andy Fleming's newspaper-tycoon father wants him to take over the family business. Andy, though, has no intention of running the paper. He's barely able to run his life--he's never paid a bill on time, routinely gets lost on the way to work, and would rather gouge out his own eyes than deal with office politics. Andy agrees to work for a year in the newsroom, knowing he'll make an ass of himself and hate every second of it. Except, Nick Russo keeps rescuing Andy: showing him the ropes, tracking down his keys, freeing his tie when it gets stuck in the ancient filing cabinets. Their unlikely friendship soon sharpens into feelings they can't deny. But what feels possible in secret--this fragile, tender thing between them--seems doomed in the light of day. Now Nick and Andy have to decide if, for the first time, they're willing to fight. --provided by publisher.